68 MHz Fundamental Repetition Rates for Mode-Locked Erbium Doped Fiber Laser based Carbon Nanotube Saturable Absorber. (April 2020) - Rifin, S N M; Munajat, Y; Razak, S N A; Zulkifli, M Z; Ahmad, H
Abstract: A carbon nanotube thin film as saturable absorber in a cavity design of mode-locked fiber laser is reported in this work. Measured by power dependent absorption setup, 22% modulation depth of the saturable absorber is estimated which is ideal for stabilizing the mode-locked operation. Based on the scanning image from atomic force microscope (AFM), Single wall carbon nanotube components are identified existed in the thin film. The laser cavity employed a ~40 cm long erbium doped fiber as a gain medium which corresponds to the laser wavelength of 1550 nm (telecommunication wavelength region). Total length cavity of the fiber laser is about 3.1 m where shorter cavity design is required for higher repetition rate. This proposed system result in a firm soliton spectrum at centre wavelength of ~1561 nm with ~0.7 mW average output power and pulse duration of 410 fs. The pulses are generated at fundamental repetition rate of 68 MHz without any distortion and excellent spectral quality.